Application of the Bang and Ramm age at death estimation method to two known‐age archaeological assemblages. Issue 3 (17th July 2014) - Tang, Nancy; Antoine, Daniel; Hillson, Simon
ABSTRACT The Bang and Ramm method uses root dentine translucency (RDT) length in sectioned or unsectioned teeth as a sole indicator of chronological age at death in adult human remains. The formulae have been tested on modern remains of known age and on modern and archaeological remains of unknown age. This is the first published study of the method on known‐age archaeological specimens and tests whether RDT is a good indicator of chronological age in buried human remains. We applied the Bang and Ramm equations to two 18th and 19th century assemblages excavated from the crypt of Christ Church, Spitalfields, and the cemetery of All Hallows by the Tower. Translucency was defined by shining a light through the external unsectioned root surface and was measured from digital images of 583 and 83 nonmolar roots from 126 Spitalfields and 12 All Hallows individuals, respectively, aged 21–81 years. Average absolute difference between real age and estimated age was 10.7 years and 8.4 years for Spitalfields and All Hallows individuals, respectively, with 58% and 75% estimated within 10 years of known age, and 29% and 33% estimated within five years of known age. These estimations are comparable to results from other ageing methods applied to the Spitalfields collection. Ages from both populations were estimated largely to the middle ranges, with younger individuals overestimated and older individuals underestimated. This is a common occurrence when using inverse calibration, where age is treated as the dependent variable and the ageing feature as the independent variable. Am J Phys Anthropol 155:332–351, 2014. © 2014 Wiley Periodicals, Inc.